Docetaxel/S-1 Versus Docetaxel/Capecitabine as First-Line Treatment for Advanced Breast Cancer: A Retrospective Study. Issue 41 (October 2015) - Li, Jinyu; You, Junhao; Si, Wen; Zhu, Yanyun; Chen, Yi; Yang, Bo; Han, Chun; Linghu, Ruixia; Zhang, Xingyang; Jiao, Shunchang; Yang, Junlan
Abstract : Abstract: The treatment efficacy of advanced breast cancer is still not promising. This study aimed to compare the efficacy and safety of docetaxel/S-1 (DS1) versus docetaxel/capecitabine (DX) as the first-line treatment for advanced breast cancer. From June 2008 to June 2013, 22 patients with advanced breast cancer were treated with the DS1 regimen. Another 26 age- and disease status-matched patients treated with the DX regimen served as controls. The 2 groups were compared in terms of time to progression (TTP), objective response rate, disease control rate, clinical benefit rate, and safety profiles. Median TTP did not differ significantly between the DS1 group and the DX group (9.04 vs 10.94 months, P = 0.473). There were no significant differences in objective response rate, disease control rate, and clinical benefit rate between the 2 groups. Both the DS1 and the DX regimens showed good tolerability. The 2 regimens showed no significant difference in adverse events except degree III hand-foot syndrome (DS1 0 vs DX 23.1%, P = 0.025). For the first-line treatment of advanced breast cancer, the DS1 and the DX regimens showed similar efficacy and safety. The DS1 regimen had less severe hand-foot syndrome than the DX regimen.